Penyuluhan tentang pentingnya aktivitas fisik dalam menjaga fungsi kognitif pada lansia dan latihan senam otak bagi lansia di panti bina usia lanjut provinsi - nasrianti; patungo, Viertianingsih (Sahabat Publikasi Kuu, 2022)
The number of elderly people in the world is increasing, including in Indonesia, which is included in the top 5 countries with the most elderly populations in the world. In 2022, it is recorded that the number of elderly (> 60 years) is 29.3 million people (10.82%) of the total population in Indonesia. The Papua Province Elderly Development Home is the only nursing home in the province of Papua with a capacity of 70 people. Currently, there are 36 elderly people. Based on Putri's research (2022) at the Nursing Home for the Elderly Province of Papua Province, it was found that most of the elderly did not have enough physical activity, which can be seen from the large number of elderly people whose daily activities are just sitting quietly and walking around in the room or outside the room. Physical exercise for the elderly at the orphanage is joint exercise to make them fresher and healthier guided by the orphanage's staff. Cognitive function problems are also starting to appear where some elderly find it difficult to concentrate or remember. This activity went well with counseling and demonstration methods which were attended by 10 orphanage staff. All the participants followed every step of the brain exercise for the elderly with great enthusiasm. It is hoped that it will not only become new knowledge for them but will become a reference for exercise that will be carried out in the future in order to maintain the freshness and health of the elderly, as well as in maintaining the cognitive function of the elderly